1991
DOI: 10.1210/endo-128-3-1209
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Glycan Moiety of the Rat Ovarian Luteinizing Hormone/Chorionic Gonadotropin (CG) Receptor and Human CG for Receptor-Hormone Interaction*

Abstract: The role of the glycan moiety of the rat ovarian LH/CG receptor and human CG (hCG) in high-affinity receptor-hormone interaction was investigated by cross-linking and quantitative binding experiments. hCG and its derivatives, desialylated hCG and deglycosylated hCG were labeled either to the alpha-subunit (125I) or the beta-subunit (3H). The ligands were attached to ovarian membrane particles, which were treated with neuraminidase or peptide-N-glycosidase F to remove terminal sialic acids or N-linked oligosacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 41 publications
0
19
1
Order By: Relevance
“…The nature of the carbohydrates of the HCG/LHR has been elucidated using specific endo-, and exo-, glycosidases. It was demonstrated that the oligosaccharide chains were susceptible to cleavage by PNGaseF (as described above; Petäjä-Repo et al, 1991), and by neuraminidase (Rajaniemi et al, 1996). In contrast, EndoH, α-mannosidase and O-glycosidase (which cleave high mannose/hybrid N-linked sugars, mannose residues from high mannose oligosaccharides and O-linked oligosaccharides respectively) did not modify the HCG/LHR carbohydrate chains (Petäjä-Repo, 1994;Rajaniemi et al, 1996).…”
Section: Lh Receptormentioning
confidence: 95%
See 1 more Smart Citation
“…The nature of the carbohydrates of the HCG/LHR has been elucidated using specific endo-, and exo-, glycosidases. It was demonstrated that the oligosaccharide chains were susceptible to cleavage by PNGaseF (as described above; Petäjä-Repo et al, 1991), and by neuraminidase (Rajaniemi et al, 1996). In contrast, EndoH, α-mannosidase and O-glycosidase (which cleave high mannose/hybrid N-linked sugars, mannose residues from high mannose oligosaccharides and O-linked oligosaccharides respectively) did not modify the HCG/LHR carbohydrate chains (Petäjä-Repo, 1994;Rajaniemi et al, 1996).…”
Section: Lh Receptormentioning
confidence: 95%
“…Exposing [ 125 I]-affinity-labelled, purified HCG/LHR to PNGaseF under limiting conditions generated a deglycosylated receptor of 62 kDa from the native 92 kDa receptor. As the fully deglycosylated receptor was produced via only 1-3 intermediates, it was concluded that not all six putative glycosylation sites were used (Petäjä-Repo et al, 1991;Petäjä-Repo, 1994). However, even if all six sites were utilized, it is unlikely that deglycosylation by PNGaseF and SDS-PAGE analysis would be sufficiently sensitive to reveal all the partially glycosylated intermediate states of the HCG/LHR.…”
Section: Lh Receptormentioning
confidence: 99%
“…However, there are several lines of evidence to indicate that both subunits interact with target cell receptors. First, cross-linking experiments indicate that both subunits are in very close proximity to the receptor (Ji & Ji 1981) and that more of the a-subunit is actually involved in the receptor interaction than the ß-subunit (Kusuda & Dufau 1986, Petaja-Repo et al 1991. Secondly, both polyclonal and monoclonal antibodies against the a-subunit block binding of native human CG (hCG) to its receptor and fail to recognise native hCG once it has bound to its receptor; some antibodies against the ß-subunit have similar effects (Moyle et al 1982, Milius et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Purified milk and salivary CA VI (1 g) were digested with PNGase F as described earlier (19), and the deglycosylated and nondeglycosylated proteins were subjected to SDS͞PAGE followed by Colloidal Coomassie staining (NOVEX, San Diego).…”
Section: Methodsmentioning
confidence: 99%